Problematika Anak Pekerja Migran di Tulungagung dalam Perspektif Bimbingan dan Konseling - Widyarto, Wikan Galuh; Rifauddin, Machsun (Jurnal Kajian Bimbingan dan Konseling, 2020)
Migrant workers are foreign exchange earners but also cause social problems, especially for children who are left behind. This study aimed to explain the problems experienced by children of migrant workers guidance and counseling point of view. A qualitative approach with a case study design was deployed in this study. Four children of migrant workers were recruited as the key informants in this study, while the supporting informants were their grandparents and mothers/fathers who take care of them at home. Data were collected using interview and List of Community Issues (LOCI). Data analysis was performed by reducing, presenting, and verifying data, as well as drawing conclusions. The validity of the data was tested using data triangulation. Findings suggest that the problems faced by children of migrant workers are health, economic, family, religion and moral problems, personal, social and organizational relationships, occupation, study habits and romance problems. These findings can be used as a basis for developing guidance and counseling programs to facilitate the growth and development of migrant workers’ children.